A critical evaluation of the law of provocation and proposals for its reform - Thrower, Tomas (2007)
In 2005, the Home Secretary commissioned a new review of the law of murder, with a view to ''resolving many of the recognised problems"^ These centred on the breadth of conduct, and the implications for the 'mandatory life' sentence, both as punishment in law, and as a social label in marking out the gravest offenders against society. It is against these difficulties that the partial defence of provocation has struggled to reliably reflect the reduced culpability of those who kill when provoked to a loss of self-control, particularly concerning situations of domestic violence. The controversial House of Lords decision in Smith led to a separate review of the partial defences. This thesis first considers the definition and scope of problems facing murder and their reform, in establishing the wider framework within which provocation must operate. It then examines problems facing present provocation, assessing the different options for reform, and introducing the experiences of other states. The previous reform dialogue suffered from an absence of common values, and so the different reform options for provocation are assessed through the application of specific criteria, enabling more objective and authoritative conclusions. These conclusions are then reassessed in light of the recommendations made regarding the reform of murder